Analisis Pelaksanaan Perkuliahan SPH II untuk Buku Ajar Perkembangan Embrio Mamalia - Ulya Ruwaida; Mohamad Amin; Umie Lestari (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This study aims to identify the need for the development of SPH II teaching materials on mammalian embryo development material. Data collection research was conducted using student questionnaire sheets. The results of the study show that 100% of students need the development of new teaching materials with research results that present applicative examples in society. As many as 57% of students stated difficulties in using available teaching materials because of the complexity of the language and the absence of evaluation. Mammalian embryo development is an elusive material (43%) and there has never been an explanation of the role of genes in the determination of mammalian twin births. The conclusion of this study is the need for the development of teaching materials in the form of textbooks based on the results of research on the detection and analysis of twin cow marker genes.Abstrak: Penelitian ini bertujuan untuk mengidentifikasi kebutuhan pengembangan bahan ajar SPH II pada materi perkembangan embrio mamalia. Pengumpulan data penelitian dilakukan dengan menggunakan lembar angket mahasiswa. Hasil penelitian menunjukkan bahwa 100% mahasiswa membutuhkan pengembangan bahan ajar baru berbasil penelitian yang menyajikan contoh aplikatif dalam masyarakat. Sebanyak 57% mahasiswa menyatakan kesulitan dalam menggunakan bahan ajar yang tersedia karena kompleksitas bahasa dan belum adanya evaluasi. Perkembangan embrio mammalia merupakan materi yang sulit dipahami (43%) dan belum pernah terdapat penjelasan mengenai adanya peran gen dalam penentuan kelahiran kembar mamalia. Kesimpulan penelitian ini adalah perlu adanya pengembangan bahan ajar berupa buku ajar berdasarkan hasil penelitian deteksi dan analisis gen penanda kembar sapi.